A CLINICAL CASE OF LOSS OF THE UPPER LATERAL INCISORS AS A RESULT OF CANINES IMPACTION. - Hristina Arnautska; Gergana Ivanova (Peytchinski Publishing, 2014)
The resorption of the lateral incisors after ectopic eruption of the permanent canines is one of the most common complications and may be detected in all cases of seriously altered route of eruption. The case presented is of a 10-year old boy with permanent dentition and extracted upper lateral incisors as a result of a severe degree of resorption of their roots due to improper eruption of the canines. This article aims at establishing that early detection and prompt preventive measures will lead to avoiding the critical complications arising out of the impacted canines and will preserve the morphological and functional integrity of the incisors and the dentition.